(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the theoretical and practical aspects of standardization, certification, and quality management systems (QMS). It analyzes their interconnection and role in ensuring the competitiveness of organizations under globalization. Special attention is given to the experience of the Republic of Uzbekistan in developing the national certification system and implementing international ISO standards. The study identifies challenges and prospects of QMS implementation and provides practical recommendations for government bodies, enterprises, and educational institutions.